Educação ambiental e direito ambiental: desvelando relações em práticas político-pedagógicas de ONGs ambientalistas - Peres, Regina Sbardelini [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
This dissertation is the result of a research of qualitative nature, in its study of case approach, that aimed to analyze the possible contributions to the political-pedagogic practices of environmental NGOs when incorporate elements of Environmental Law. It has as unity of analysis a program of mobilization and monitor work about the quality of Tiete River s water, developed by an environmental NGO with the participation of several social actors. The analysis was accomplished since the collected datum in the interviews, in the remarks and documents. It was verified that the incorporation of the Environmental Law in the program in question materializes by different means and that necessarily do not exclude themselves. These means are moments that the environmental juridical field but this it makes present as environmental laws, but that as explanation of concepts and courses, but, still, as an instrument for the solution of social- -environmental conflicts. Regarding to the characteristics that the political-pedagogic practices of Environmental Education acquires when they incorporate elements of Environmental Law, it was verified that this issue is intrinsically related to the degree of interface of the environmental juridical field in the regarded practices. Thus, if the interface is tenuous and moderate, merely annexing information, the informative character prevails, however, if this interface structure wider than the others ones, being the Environmental Law utilized as instrument of fronting the social- -environmental conflicts, the politics dimension emerges, becoming itself the main characteristic of these practices, justifying them as political- -pedagogic practices. The result obtained with the research demonstrated that the incorporation of the Environmental Law by Environmental Education is as possible as necessary because it becomes a concrete perspective of aggregation with a greater consistency.
Keywords: Educação ambiental; Direito ambiental; ONGs ambientalistas; Práticas-político-pedagógicas; Environmental Education; Environmental Law; Environmental NGOs; Political-pedagogic Practices